1990
DOI: 10.1073/pnas.87.23.9088
|View full text |Cite
|
Sign up to set email alerts
|

A nervous system-specific isotype of the beta subunit of Na+,K(+)-ATPase expressed during early development of Xenopus laevis.

Abstract: We have previously described the isolation of several genes expressed exclusively in the nervous system of adult Xenopus laevis and activated in the embryo shortly after neural induction. The sequence of one of these cDNAs, 24-15, identifies the corresponding protein as an isotype of the (3 subunit of Na',K+-ATPase [ATP phosphohydrolase (Na+/ K+-transporting); EC 3.6.1.37]. This form is distinct from the previously described (31 subunit of Xenopus, and the protein sequence comparison suggests that it is not th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(49 citation statements)
references
References 47 publications
1
48
0
Order By: Relevance
“…In outside-out patches excised from uninjected Xenopus oocytes, the presence of 100 M ouabain effectively prevents current signals from endogenous, ouabain-sensitive, Xenopus Na͞K pumps (believed to comprise Xenopus ␣1 and ␤3 subunits (19,20) in response to application of picomolar concentrations of PTX (see Fig. 8, which is published as supporting information on the PNAS web site).…”
Section: Resultsmentioning
confidence: 99%
“…In outside-out patches excised from uninjected Xenopus oocytes, the presence of 100 M ouabain effectively prevents current signals from endogenous, ouabain-sensitive, Xenopus Na͞K pumps (believed to comprise Xenopus ␣1 and ␤3 subunits (19,20) in response to application of picomolar concentrations of PTX (see Fig. 8, which is published as supporting information on the PNAS web site).…”
Section: Resultsmentioning
confidence: 99%
“…At least two types of isoforms, (31 and (32, have been characterized in rats by cDNA cloning ( 11), and recently the existence of the (3 isoform has been reported ( 12). The function of the subunit remains unknown, but it has been suggested that the subunit plays a role in the integration of the a subunits into the membrane (6).…”
Section: Discussionmentioning
confidence: 99%
“…The near full-length a, cDNA (-45 to +3349 bp = &wt) from Xcnopus laevis previously cloned from an A6 kidney cell library [9] and a /3x cDNA cloned from a Xenopus neurula library [7,8] were inserted into the pSDS vector [6]. We have previously shown that both the PI September 1991 Fig.…”
Section: Deletion Mutnnl At the N Terminus Of The ~1 Isofarmmentioning
confidence: 99%